Spectrum Defragmentation Algorithm based on Fragmentation Index in Intelligent Elastic Optical Network - WANG Feng; LIU Minyu; YU Xiaosong; ZHAO Yongli (Guangtongxin yanjiu)
【Objective】As a new optical communication technology, intelligent elastic optical network provides higher bandwidth and flexibility to meet the increasing demand of power communication. However, due to the uneven spectrum demand size and distribution of different communication requests, it may lead to fragmentation of spectrum resources in the network. These fragmented spectrum resources may result in the waste of spectrum resources and the degradation of network performance.【Methods】This paper introduces an evaluation method of fragmentation index, and takes it as a reference to judge whether to carry out spectrum defragmentation operations for running services.【Results】The simulation results show that compared with the traditional algorithm, the bandwidth blocking rate can be reduced by 5% to 30%. It is also shown that the the bandwidth blocking rate reduction is more obvious when the traffic volume is larger.【Conclusion】The algorithm proposed in this paper comprehensively considers the proportion of spectrum fragments on a single fiber, the average frequency gap of services on the link, and the occupation weight of each time slot in each fiber core. This paper also evaluates the frequency gap occupation of the network from a multidimensional perspective, providing an efficient optimization scheme for resource allocation.